Comparative study of the clinical laboratories in Iloilo City - Allones, Mary Grace; Mogote, Jeanny Rose; Pagunsan, Doree Jane; Tolosa, Locel
Executive summary-The researchers conducted a Comparative Study on the different clinical Laboratories in Iloilo City. The study aims to inform the customers and recommend a clinical laboratory that offers quality service at a reasonable price. Based on the gathered data, the researchers identify various factors that affect the customer preferences. These are the facilities, equipment, services offered, location, personnel and prices. Each clinical laboratory was ranked according to these factors. The researchers were able to choose a clinical laboratory, which meet all these requirements.